LA OCUPACIÓN INCA EN CONVENTOMOQO, VALLE DEL CUSCO - Delgado González, Carlos (2014)
The research was part of a proposed bailout of 2007, made in one of the many archaeological sites that are being occupied by the increasing urbanization for the slopes of the valley of Cusco. With the arrival of the Spaniards to the city of Cusco, this place was densely occupied, both the central core, as in the surrounding area of the city where the population lived in villages. Conventomoqo was a small domestic village in the the right margin of the Huatanay River, and it was settled on a hill in an area that was already previously occupied from the formative period. The radiocarbon dated obtained in the place show that this place is late and would be placed in the Inca period-colonial, agreeing with the idea that the populations continued to occupy these places until the viceroy Toledo, in 1572, he makes the reduction in eight parishes of the Inca peoples who lived on the outskirts of the city. The archaeological record identified several events of abandonment of this place that are embodied in the present work.